Ray-Tracing-Based Modeling of Clad-Removed Step-Index Plastic Optical Fiber in Smart Textiles: Effect of Curvature in Plain Weave Fabric - Sun Hee Moon; Joon Seok Lee; In Hwan Sul (Advances in Materials Science and Engineering)
Plastic optical fiber was chosen for information delivery media in smart textile. Cladding layer was peeled off by chemical and mechanical methods to find optimal peeling conditions. Both radial side illumination and longitudinal end-tip illumination were measured for visible light of 627 µm wavelength. A half-cone-shaped jig was manufactured using 3D printing to give various curvature conditions to fibers. Also POFs were embedded in plain weave textile structure to measure the light dissipation effect. The waveguide phenomenon was modeled using discrete ray tracing technique and ray-to-interface collision detection algorithm. Results from the proposed modeling technique showed linear relationship with those from experiment.